Molecular characterization of rice genotypes for Zinc biosynthetic gene(s) using microsatellite simple sequence repeat (SSR) markers - Mia, Md Mukul; Rahman, Shanjida; Islam, Mirza Mofazzal; Begum, Shamsun Nahar; Hassan, Lutful (Asian Journal of Medical and Biological Research, 2015)
Zinc deficiency is prevalent and affects nearly two billion people in the developing world, where mainly cereals are consumed as staple food by the people. It is essential to study the genetic characters of the rice genotypes containing genes responsible for zinc synthesis so that they can be used as breeding resource to develop nutrient rich rice varieties. In this study, 46 rice (Oryza sativa L., 2n=24) genotypes were studied for their Zinc biosynthesis ability using 3 Rice Microsatellite (RM) markers (RM23, RM217 and RM35) linked to Zn content at Biotechnology Laboratory of Bangladesh Institute of Nuclear Agriculture (BINA) and Genetics and Plant Breeding Laboratory of Bangladesh Agricultural University, Mymensingh during 5 August, 2013 to 30 April, 2014. The DNA samples were isolated by CTAB mini-prep method from 21 days older rice leaf samples followed by Polymerase chain reaction (PCR). Three markers (Rm23, RM35 and RM217) showed effective polymorphism in DNA band appearance for Zn content out of ten SSR markers. The alleles were separated on Polyacrylamide Gel Electrophoresis (PAGE) system. After molecular analyses of DNA bands using Power Marker software, variation was found in allele number, allele frequency, polymorphism information content (PIC) and gene diversity for each genotype. Number of alleles (23, 19 & 13), PIC-polymorphism information content (0.946, 0.911 & 0.829), gene diversity (0.948, 0.917 & 0.846), rare allele (16, 12 & 8) and null allele (0, 16 & 2) were observed for 3 rice microsatellite (RM) markers viz. RM35, RM217 and RM23, respectively for the 46 rice genotypes. A total of 55 alleles were found by using 3 SSR primers for all genotypes. The number of alleles per locus ranged from 13 to 23 with an average of 18.33 out of total 55 alleles. The UPGMA Dendrogram categorized all the varieties into 7 distinct clusters based on 50% of average genetic distance among the 46 genotypes (Figure 2 and Table 7). Since the primers showed almost similar and highest PIC values, based on this study, the larger range of similarity values using SSR markers will provide greater confidence for the assessment of genetic relationships among the varieties. The information obtained from SSR profiling helped in identifying the varieties containing genes for Zn synthesis among the selected rice genotypes. Among all the rice genotypes, Kumra Ghor, Ghigoj, Tilek Kuchi contained high Zn content found in another chemical analysis. Most of the genotypes contained candidate gene for Zn synthesis and can be used as breeding materials to develop nutrient (Zn) rich rice varieties through different selective breeding methods in future. Asian J. Med. Biol. Res. June 2015, 1(2): 187-197